2014
DOI: 10.1051/epjconf/20146702095
|View full text |Cite
|
Sign up to set email alerts
|

Tests of thermal resistance of simulated walls with the reflective insulation

Abstract: Abstract. The paper presents the thermal resistance characteristics of walls with multilayer reflective insulation. The tests have been performed using a heat flow meter to determine the resistivity of the layers simulating partition walls in buildings. A modification of the structure has also been proposed and analysed with a view to increase the thermal resistance and, consequently, reduce the heat flux transferred through the walls. Consequently, walls produced with layers that ensure higher thermal insulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
(5 reference statements)
0
13
0
Order By: Relevance
“…Despite many studies conducted in educational buildings, very few deal with modern, intelligent buildings. The present study aims to provide additional knowledge in this area, especially that modern buildings are built with new materials and technologies (as indicated by Piotrowski et al [25]).…”
Section: Introductionmentioning
confidence: 99%
“…Despite many studies conducted in educational buildings, very few deal with modern, intelligent buildings. The present study aims to provide additional knowledge in this area, especially that modern buildings are built with new materials and technologies (as indicated by Piotrowski et al [25]).…”
Section: Introductionmentioning
confidence: 99%
“…This means that 25 % of people were dissatisfied with the conditions in the room. The study by Majewski et al [13] additionally confirms that statistically men feel more comfortable than women. The graph below (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Ji et al [11] showed that the human body is more sensitive to cold temperatures than to warm ones. Based on the papers [12,13], it can be concluded that air temperature and humidity have the greatest influence on the thermal sensations. Thus, changes in temperature affect the impression of thermal comfort.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements were found to be very useful for determining the actual thermal performance of the exterior walls in existing buildings, especially since the values determined on-site in buildings in the actual conditions would often significantly differ from the calculated ones. In the subsequent years, several experimental and computational studies aimed at determining the total thermal resistance of walls, using the approach for heat flow steady state, including reviews of the measurement methods [ 8 , 9 ], methodology [ 10 , 11 , 12 , 13 ], the use of in situ methods [ 2 , 14 , 15 , 16 , 17 ] and unsteady state conditions [ 18 , 19 , 20 , 21 ], were carried out.…”
Section: Introductionmentioning
confidence: 99%